Distinctive qualities in communication research - Carbaugh, Donal A.; Buzzanell, Patrice M. (Routledge, 2010)
This timely volume provides an in-depth look at why the field of communication is so central in initiatives for social impact around the world. Editors Donal Carbaugh and Patrice M. Buzzanell bring together scholars with varied and productive approaches to communication to address the question of what distinguishes communication research from similar studies in other disciplines. The work provides an invaluable resource for defining the role of communication research in the academic community and the contributions it makes to the study of human interaction.